Хромосомо-генна теорія електромеханічних систем на прикладі електромеханічних дезінтеграторів - Лущик, В'ячеслав Данилович (НТУ "ХПІ", 2012)
Обґрунтовується неефективність і непрацездатність електромеханічних дезінтеграторів, розроблених з допомогою хромосомо-генної теорії. Зроблений висновок про безплідність хромосомо-генної теорії в електромеханічній науці.

Inefficiency and nonserviceability of the electromechanical disintegrators developed by means of a chromosomal-genetic theory is justified. Conclusions are made about futility of the chromosomal-genetic theory in electromechanical science.
A chromosomal-genetic theory of electromechanical systems by the example of electromechanical disintegrators
Keywords: Шинкаренко Василь Федорович; монографія; критика; біологія; генетика; електротехніка; машини електричні; chromosomal-genetic theory; electromechanical disintegrators; three-phase winding; futility